Hepatitis C Virus Infection and Dialysis: 2012 Update. (17th December 2012) - Fabrizi, Fabrizio
Abstract : Hepatitis C virus infection is still common among dialysis patients, but the natural history of HCV in this group is not completely understood. Recent evidence has been accumulated showing that anti-HCV positive serologic status is significantly associated with lower survival in dialysis population; an increased risk of liver and cardiovascular disease-related mortality compared with anti-HCV negative subjects has been found. According to a novel meta-analysis (fourteen studies including 145, 608 unique patients), the adjusted RR for liver disease-related death and cardiovascular mortality was 3.82 (95% CI, 1.92; 7.61) and 1.26 (95% CI, 1.10; 1.45), respectively. It has been suggested that the decision to treat HCV in patients with chronic kidney disease be based on the potential benefits and risks of therapy, including life expectancy, candidacy for kidney transplant, and co-morbidities. According to recent guidelines, the antiviral treatment of choice in HCV-infected patients on dialysis is mono-therapy but fresh data suggest the use of modern antiviral approaches (i.e., pegylated interferon plus ribavirin). The summary estimate for sustained viral response and drop-out rate was 56% (95% CI, 28–84) and 25% (95% CI, 10–40) in a pooled analysis including 151 dialysis patients on combination antiviral therapy (conventional or pegylated interferon plus ribavirin).